Пошаговое объяснение:
1
1) 8а+19а-28а+3а= 2а
2) -4х+11х+35х-38х= 4х
3) 14а-а+в-26в= 13а+(-25в)= 13а-25в
4) 1,6с-1,2-3,1+0,8 = 1,6с - (1,2+3,1-0,8)= 1,6с-3,5
5)2,6а-5,4с-а+2с= 1,6а-3,4с
6)‐9у+12у-41у-17у=-55у
7)8х-17х-19+21х= 10х-19
8)-5,6к+4,8+8,2к-9,1= 2,6к-4,3
9)-8х+16х-23х+17х= 2х
10)5х-5-4х-8+3х= 4х-13
2
1)3(х+у+с)= 3х+3у+3с
2)(х+у+с)•4= 4х+4у+4с
3)3(2х-3у+4с)= 6х-9у+12с
4)-3(-3х+5у-4к+с)= 9х-15у+12к-3с
5) (5х+2у-с)•(-2)= -10х-4у+2с
6)5(2а+в-8с)= 10а+5в-40с
7) -4(-х+3у-4к)= 4х-12у+16к
8) не видно
9)9у-5(12-х)= 9у-60+5х
10)-4(5х+9у-к) = -20х-36у+4к
3
1)3(х+6)-х-2(х+9)= 3х+18-х-2х-18=3х-3х+18-18=0
2)не видно
3) (8х+3)-(10х-6)-9= 8х+3-10х+6-9= -2х
4)не видно
5)(7х+1)-(9х+3)+5= 7х+1-9х-3+5= -2х+3
6)не видно
7)4(5х+2)-10(3х-2)+15= 20х+8-30х+20+15= -10х+43
8)не видно
9)5,6-3(2-0,4х)-0,4(4х-1)= 5,6-6+1,2х-1,6х+0,4= -0,4х
10)5(х-12)+6(х-10)-(х-1)= 5х-60+6х-60-х+1= 10х-119